2006
DOI: 10.1074/jbc.m510623200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Folate-mediated One-carbon Metabolism by 10-Formyltetrahydrofolate Dehydrogenase

Abstract: 10-Formyltetrahydrofolate dehydrogenase (FDH) catalyzes the NADP؉ -dependent conversion of 10-formyltetrahydrofolate to CO 2 and tetrahydrofolate (THF) and is an abundant high affinity folatebinding protein. Although several activities have been ascribed to FDH, its metabolic role in folate-mediated one-carbon metabolism is not well understood. FDH has been proposed to: 1) inhibit purine biosynthesis by depleting 10-formyl-THF pools, 2) maintain cellular folate concentrations by sequestering THF, 3) deplete th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 28 publications
(45 reference statements)
4
87
0
Order By: Relevance
“…Although the binding between GNMT and 5-methyl-THF has been well characterized, the significance of maintaining optical folate status in human pathological conditions is less clear, and the specific impact of GNMT expression on hepatic methylfolate-dependent reactions has not been elucidated. In recent years, stable isotope tracers have been widely utilized to elucidate how specific folate enzymes mediate and regulate the fluxes of one-carbon units among folate-dependent reactions (19)(20). We demonstrated that transformed human lymphoblasts with reduced methylene tetrahydrofolate reductase (MTHFR) have advantages in de novo purine synthesis when folate is adequate, but they are more susceptible to S-adenosylmethionine depletion when folate is restricted (21).…”
Section: Gnmt Expression Increases Hepatic Folate Contents and Folatementioning
confidence: 99%
“…Although the binding between GNMT and 5-methyl-THF has been well characterized, the significance of maintaining optical folate status in human pathological conditions is less clear, and the specific impact of GNMT expression on hepatic methylfolate-dependent reactions has not been elucidated. In recent years, stable isotope tracers have been widely utilized to elucidate how specific folate enzymes mediate and regulate the fluxes of one-carbon units among folate-dependent reactions (19)(20). We demonstrated that transformed human lymphoblasts with reduced methylene tetrahydrofolate reductase (MTHFR) have advantages in de novo purine synthesis when folate is adequate, but they are more susceptible to S-adenosylmethionine depletion when folate is restricted (21).…”
Section: Gnmt Expression Increases Hepatic Folate Contents and Folatementioning
confidence: 99%
“…31 The enzyme functions as a metabolic regulator, which removes carbon groups, in the form of CO 2 , from the reduced folate pool, thus diverting them from biosynthetic pathways. 32,33 This function results from FDH-catalyzed reaction of the conversion of 10-formyltetrahydrofolate (10-fTHF) to tetrahydrofolate (THF) and CO 2 in a NADP + -dependent manner. 33 FDH, being abundant in normal tissues, is commonly down-regulated or silenced in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the enzymatic function of FDH, that is the conversion of 10-formyltetrahydrofolate to tetrahydrofolate, was known for decades, the main physiological role of the enzyme is still in question. Proposed FDH functions include regulation of reduced folate pools (Champion et al, 1994), storage of the intracellular folate (Min et al, 1988), regulation of de novo purine biosynthesis (Krupenko and Oleinik, 2002) and regulation of cellular methylation (Anguera et al, 2006).…”
Section: Introductionmentioning
confidence: 99%